Tropical diseases and the gastrointestinal tract: an overlooked connection - Ghazy, Ramy Mohamed; Alshaikhi, Saleh Ahmed; Assiri, Hassan Ahmed Hassan; Almozaini, Adel Ahmed; Alhazmi, Abdullah Faisal; Elhasaneen, Heba Elsaeed Mohammed; Abdo, Sarah M. (Frontiers in Tropical Diseases, 2025)
BackgroundTropical infectious diseases continue to impose a significant public health burden, particularly in regions with poor sanitation, limited healthcare access, and favorable environmental conditions for pathogen transmission. Gastrointestinal (GI) involvement is a key clinical feature across many of these diseases, contributing significantly to global morbidity and mortality. Despite increasing awareness, few existing reviews comprehensively integrate the pathophysiology of GI involvement, diagnostic challenges, and multidisciplinary public health strategies, including the One Health approach.MethodsThis narrative review synthesizes current evidence on tropical diseases with GI manifestations. A structured literature search was conducted using major databases. Key themes were identified through thematic synthesis, including disease mechanisms, diagnostic limitations, treatment options, and prevention strategies.ResultsA significant number of tropical diseases spread through the fecal-oral route, primarily due to contaminated food or water, particularly in areas with poor sanitation. These include helminthic, protozoal, bacterial, and viral infections. Vector-borne diseases and zoonotic infections also present substantial GI involvement. Chronic parasitic presence triggers inflammation, fibrosis, and oxidative stress, leading to tissue damage and long-term complications, including cancers. Misdiagnosis of GI symptoms as more common conditions like irritable bowel syndrome delays appropriate care and worsens outcomes. The globalization of travel and commerce has widened the spread of these diseases, with travelers, immigrants, and refugees frequently exhibiting unfamiliar GI symptoms in non-endemic regions.ConclusionA multifaceted strategy is essential for effective management, including improved sanitation, enhanced diagnostic tools, mass drug administration, and vector control. The One Health framework provides a sustainable model by integrating human, animal, and environmental health perspectives. Aligning interventions with global targets such as the Sustainable Development Goals (SDGs) and the WHO’s 2030 roadmap for neglected tropical diseases (NTDs) can reduce health disparities, improve nutrition, and strengthen resilience against emerging threats.